In situ neutron diffraction studies of operating MGA thermal storage materials - Sugo Heber; Kisi Erich; Bradley James; Fiedler Thomas; Luzin Vladimir (Renewable Energy and Environmental Sustainability, 2017)
Miscibility Gap Alloys (MGA) store energy as the latent heat of fusion of a discrete component within an engineered multicomponent microstructure. The thermal energy density is augmented by the associated sensible heat of the whole alloy. MGA microstructures are organised so that the low melting point component, acting as a Phase Change Material (PCM), is present as dispersed, non-intersecting particles within a continuous 3-dimensional solid matrix of a higher melting point component. The primary advantages of such an arrangement are the high thermal conductivity, 60–200 W/m K and high energy density (0.25–1.26 MJ/L). Long service life, low maintenance and the resulting simplified infrastructure offered by the ability of the MGA storage materials to exchange heat via conduction alone are further notable benefits. Unlike sensible heat storage materials, temperature measurement alone cannot indicate the state-of-charge of PCM storage since the temperature remains relatively constant throughout the melting or freezing transition. The work reported here addresses this issue through the use of in situ neutron diffraction to determine the relative volume fractions of solid (crystalline) and liquid PCM within the MGA material as a function of varying temperature conditions. The aim is to provide calibration data for state-of-charge thermal models of PCM storage systems. Preliminary analysis of the neutron diffraction results and associated thermal measurements from a series of experiments carried out using the KOWARI diffractometer at the Australian Nuclear Science and Technology Organisation are presented in this work.